MEMANFAATKAN BIG DATA DAN SISTEM INFORMASI MANAJEMEN UNTUK KELINCAHAN STRATEGIS: TREN DAN TANTANGAN DALAM EKONOMI DIGITAL - Mayar Mohammed Sabah Ali Alkaabi; Arjuna Rizaldi; Dina Novianty (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Komputer Indonesia, 2026)
The digital economy has changed the way businesses understand and manage risk, and this has made the combination of Big Data Analytics (BDA) and Management Information System (MIS) fundamental to any organization. This research focuses on how the combination of BDA and MIS facilitates strategic agility in digitally led companies. This research utilizes the PRISMA framework in conducting a systematic literature review of 20 peer-reviewed articles between 2020 and 2025 sourced from Google Scholar. The research shows that while MIS integrates data within organizational frameworks, structures, and governance, data analytics increases the organization’s strategic sensing and forecasting interpretive abilities. While Strategic agility has been identified within the literature as a mediating capability explaining the relationship between the adoption of digital technologies and the improvement of organizational outcomes, and not as a direct result of its adoption, the literature does present a paradox, characterized by complex data governance, skill gaps, limited interoperability, and excessive analytical dependence that may narrow scope for managerial discretion. Keywords: Big Data Analytics, Digital Economy, Management Information Systems, Strategic Agility, Systematic Literature Review